GENDER INEQUALITY IN SOUTH AFRICAN MUNICIPALITIES - Vyas-Doorgapersad S (RADJA PUBLIKA, 2023)
Because they are frequently disenfranchised at societal, business, commercial, intellectual, bureaucratic, and political levels, women still hold lower status as professionals. Africa is not atypical of the trend of gender inequality that is pervasive throughout the world. Politics, which has predominantly masculinized in the continent and has only allowed women to provide preventive care within their own homes, is still being prohibited to women. The rationale is that in a patriarchal society, a woman's value is to care for the house, whereas a man can serve in the political spotlight. Women’s representation and participation in political decision-making structures and processes are a matter of continuous discussion. Even African countries have legislative frameworks, and institutional processes in place, the gap of gender disparity is not reducing. The situation in South Africa is challenging as the society still follows patriarchal and stereotypical mindset, has cultural and traditional norms that may restrict women to be superior and higher in professional portfolios. The situation gets more dire at lower government level due to the lack of understanding of gender roles, responsibilities, and contribution that women may bring as political office-bearers. The political level of gender disparity in South African municipalities is examined in this article. It discusses the challenges that local governments encounter regarding electing women on political decision-making levels. The article therefore explains the factors that lead to gender inequality difficulties and suggests the types of support or resources needed to promote gender equality in political portfolio in South African municipalities.